2019
DOI: 10.1080/17436753.2019.1667175
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of TiC-TiB2 composite ceramic tool and its cutting performance in turning austenitic stainless steel

Abstract: New TiC-TiB 2 ceramic cutting tool materials TiC-TiB 2 -Ni-Mo (TBNM8) and TiC-TiB 2 -Ni (TBN5) with high comprehensive mechanical properties were fabricated by hot pressed sintering with the optimised sintering processes. The cutting performance of TBNM8 in continuously turning austenitic stainless steel (1Cr18Ni9Ti) was experimentally investigated. With the optimal cutting parameters, the cutting performance of TBN5 and commercial tool LT55 were compared in wet and dry turning 1Cr18Ni9Ti. The failure mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…12,13 High-performance Si 3 N 4 tools for cutting ductile cast iron require a combination of high hardness and high toughness. 14,15 Hardness plays a critical role in wear resistance, whereas toughness is essential for anti-chipping properties. [16][17][18] Under interrupted cutting conditions, the cutting edge of the tool experiences impact loads, making it vulnerable to collapse and failure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12,13 High-performance Si 3 N 4 tools for cutting ductile cast iron require a combination of high hardness and high toughness. 14,15 Hardness plays a critical role in wear resistance, whereas toughness is essential for anti-chipping properties. [16][17][18] Under interrupted cutting conditions, the cutting edge of the tool experiences impact loads, making it vulnerable to collapse and failure.…”
Section: Introductionmentioning
confidence: 99%
“…Cutting contrast tests have demonstrated that Si 3 N 4 tools have better machining surface quality and longer cutting life than other tools during machining ductile cast iron 12,13 . High‐performance Si 3 N 4 tools for cutting ductile cast iron require a combination of high hardness and high toughness 14,15 . Hardness plays a critical role in wear resistance, whereas toughness is essential for anti‐chipping properties 16–18 .…”
Section: Introductionmentioning
confidence: 99%